Better governance in academic health sciences centres: moving beyond the Olivieri/Apotex Affair in Toronto. Issue 1 (10th February 2004) - Ferris, L E; Singer, P A; Naylor, C D
Abstract : The Toronto experience suggests that there may be several general lessons for academic health sciences complexes to learn from the Olivieri/Apotex affair (OAA) regarding the ethics, independence, and integrity of clinical research sponsored by for profit enterprises. From a local perspective, the OAA occurred when there already was a focus on the complex and changing relationships among the University of Toronto, its medical school, the fully affiliated teaching hospitals, and off campus faculty because of intertwined interests and responsibilities. The OAA became a catalyst that accelerated various systemic reforms, particularly concerning academic/industry relations. In this article, the evolving governance framework for the Toronto academic health sciences complex is reviewed and these policy and process reforms discussed. These reforms have created collaborative activity among research ethics boards and contract research offices of the partner institutions, and allowed the joint university/hospital ethics centre to play a role in governance and policy, while respecting the missions and mandates of the involved institutions. Although few of the policies are dramatically innovative, what is arguably novel is the elaboration of an overarching governance framework that aims to move ethics to a central focus in the academic complex. Time alone will tell how sustainable and effective these changes are.